(untitled) (Journal of Ideas in Health, 2021)
Currently, there is a persisting dispute regarding the renin-angiotensin-aldosterone-system (RAAS) inhibitors’ safety of use in COVID-19 pandemics. On one side, RAAS inhibitors appear to determine an overexpression of ACE2, the receptor of SARS-CoV-2. Therefore, they could increase the risk of SARS-CoV-2 infection and its degree of severity. On the other side, the discontinuation of RAAS leads to cardiovascular decompensation and has been discouraged by the major medical societies. Also, large-cohort studies report beneficial or at least neutral effects for the RAAS inhibitors in COVID-19 patients. Worldwide, millions of patients receive RAAS inhibitors for the treatment of hypertension and other important comorbidities. In this context, knowledge of the exact effect of these medications becomes of crucial significance. This paper aims to fill in a gap in the current knowledge and presents a putative mechanism by which RAAS inhibitor administration’s beneficial results can be explained better. RAAS inhibitors can be beneficial, as they counteract the excessive detrimental activation of the classical angiotensin-converting enzyme (ACE) axis, decreasing the angiotensin II levels. The angiotensin receptor blockers (ARBs) increase the angiotensin II levels, while the angiotensin-converting enzyme inhibitors (ACEI) increase the angiotensin I levels; these substrates will compete with the SARS-CoV-2 for the ACE2 binding, decreasing the viral infectivity. In addition, following the RAAS inhibitors treatment, the up-regulated ACE2 will cleave these substrates (angiotensin I and II), particularly to angiotensin 1-7 that possesses vasodilator, protective effects.